Pemberdayaan Masyarakat Dalam Implementasi Manajemen Berbasis Sekolah Di SMA Negeri 1 Geyer Grobogan - Mugiraharjo, Didik, Prof. Dr. Sutama.M.p.d, Dr.Sabar Narimo,M.,M.Pd (2017)
There are three purposes of this research. (1) Describe the effort of school to empower parents for the implementation of school based manajemen . (2) Describe the effort of school to empower school committee for the implementation of school based manajemen. (3) Describe the effort of school to empower community leaders for the implementation of school based management. The type of research is qualitative.The technique of collecting data uses observation, interviews and documentation. Data analysis techniques uses data collection, data reduction, data presentation, and conclusion. The validity test uses triangulation. There are three results of this research. (1) involve parents in planning, implementation and evaluation of school programs. The empowering parents by (a) increase the participation. (b) communicate to get the support, (c) receive aspiration (d) involve in extracurricular activities. (2) increase the role and function of school committee. The empowering school committee by (a) hold a meeting once in three months (b) encourage committee to get education resources (c) involve the committee in evaluating progress. (d) act the complaint, criticisms, and aspirations. (3) increase the participation of community leaders. The empowering community leaders by doing activities such as the socialization of traffic rules, basic leadership training , juvenile delinquency and generation planning (genre).